Structural and electrical properties of La0.7Ca0.3MnO3 /α-Fe2O3 composites - Lau, Lik Nguong; Lim, Kean Pah; Ishak, Amirah Natasha; Awang Kechik, M. M.; Chen, Soo Kien; Ibrahim, Noor Baa'yah; Shaari, Abdul halim; Lim, Eijin (Scientific.Net, 2021)
Colossal magnetoresistive (CMR) materials have huge potential in modern application and it has been widely used in magnetic sensing industry. From the literature, an incorporation of secondary insulating phase into mixed-valence manganites could improve its extrinsic effect especially low-field magnetoresistance (LFMR). However, nanoparticle addition could lead to substitution and diffusion with its parent compound. In this work, the structural and electrical properties of La0.7Ca0.3MnO3 (LCMO) were investigated by adding the α-Fe2O3 nanoparticle with ratio of 0.00, 0.05, 0.10, 0.15 and 0.20 as the artificial grain boundaries. The LCMO compound has been synthesised using sol-gel route. The samples were chosen to sinter at 800°C to obtain the pure LCMO phase by referring to the thermogravimetric analysis (TGA). The structural properties were investigated by an X-ray diffractometer (XRD) while electrical properties were measured by a four-point probe (4PP) system. XRD patterns showed the coexistence of two phases (LCMO & α-Fe2O3). LCMO crystallised in orthorhombic structure with space group Pnma while α-Fe2O3 exhibited in hexagonal form with space group R-3c. As the content of α-Fe2O3 increases, the resistivity of the samples increases drastically. Nevertheless, the addition of iron oxide has no significant effect on the metal-insulator transition temperature (TMI). From the XRD and 4PP analysis, it can be deduced that the α-Fe2O3 nanoparticles do not react with LCMO compound and successfully formed the La0.7Ca0.3MnO3 /α-Fe2O3 composites. The resistivity increases when the nano-sized α-Fe2O3 is added into LCMO nanocomposites due to the insulator nature of α-Fe2O3.